2011
DOI: 10.1016/j.taap.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Sodium arsenite delays the differentiation of C2C12 mouse myoblast cells and alters methylation patterns on the transcription factor myogenin

Abstract: Epidemiological studies have correlated arsenic exposure with cancer, skin diseases, and adverse developmental outcomes such as spontaneous abortions, neonatal mortality, low birth weight, and delays in the use of musculature. The current study used C2C12 mouse myoblast cells to examine whether low concentrations of arsenic could alter their differentiation into myotubes, indicating that arsenic can act as a developmental toxicant. Myoblast cells were exposed to 20 nM sodium arsenite, allowed to differentiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…CpGs − 76 and + 2 on myogenin gene, which were also hypermethylated, are in close proximity to the binding sites of SIX1 (sine oculis homeobox 1) and MEF2 (myocyte-specific enhancer factor) which are proven to be essential for the transactivation of myogenin gene (Palacios et al, 2010). It is surprising that CpG − 205 on myogenin gene promoter was significantly hypomethylated in PRDM16-overexpressing cells, but similar result was reported in sodium arsenite-induced delay in myogenesis (Steffens et al, 2011), thus we speculate that CpG − 205 might be or conformationally close to a binding site of a transcription repressor. PPARγ transcription was validated to be negatively related with the methylation status of its promoter in visceral adipose tissue of a diabetic mouse model (Fujiki et al, 2009) and a fat chicken line (Sun et al, 2014) where PPARγ was preternaturally activated.…”
Section: Discussionsupporting
confidence: 59%
“…CpGs − 76 and + 2 on myogenin gene, which were also hypermethylated, are in close proximity to the binding sites of SIX1 (sine oculis homeobox 1) and MEF2 (myocyte-specific enhancer factor) which are proven to be essential for the transactivation of myogenin gene (Palacios et al, 2010). It is surprising that CpG − 205 on myogenin gene promoter was significantly hypomethylated in PRDM16-overexpressing cells, but similar result was reported in sodium arsenite-induced delay in myogenesis (Steffens et al, 2011), thus we speculate that CpG − 205 might be or conformationally close to a binding site of a transcription repressor. PPARγ transcription was validated to be negatively related with the methylation status of its promoter in visceral adipose tissue of a diabetic mouse model (Fujiki et al, 2009) and a fat chicken line (Sun et al, 2014) where PPARγ was preternaturally activated.…”
Section: Discussionsupporting
confidence: 59%
“…During revision of this manuscript, Steffens et al reported that exposure of C2C12 cells to sodium arsenite delayed DM-induced differentiation [31]. Increased methylation of the same 12 CpG sites at the Myog promoter that we describe here correlated with a reduction in Myog transcription, which may consequently lead to a delay in myogenic differentiation [31].…”
Section: Discussionmentioning
confidence: 52%
“…During revision of this manuscript, Steffens et al reported that exposure of C2C12 cells to sodium arsenite delayed DM-induced differentiation [31]. Increased methylation of the same 12 CpG sites at the Myog promoter that we describe here correlated with a reduction in Myog transcription, which may consequently lead to a delay in myogenic differentiation [31]. Generally, the number of methylated CpGs and the methylation levels of CpG sites appear to coordinately control gene transcription in cells and tissues, although the molecular mechanism underlying this phenomenon remains poorly understood [13,30].…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that lower concentrations of inorganic arsenic (0.02-0.5 lM) inhibit the myoblast differentiation (Steffens et al 2011;Yen et al 2010). Li et al (2010) reported that higher concentrations of As 2 O 3 (4-32 lM) obviously reduced smooth muscle cell viability in a concentration-dependent manner ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to arsenic via drinking water has known to be associated with numerous cancers (e.g., skin, lung, and bladder) and non-cancer harmful health (e.g., skin lesions, peripheral vascular disease, cardiovascular disease, and diabetes mellitus) (Navas-Acien et al 2005;Yoshida et al 2004). Previous studies have demonstrated that low dose of inorganic arsenic is capable of inhibiting myoblast differentiation (Steffens et al 2011). Arsenic trioxide is known to be used to treat acute promyelocytic leukemia and can induce apoptosis in various cancer and normal cell lines Florea et al 2007;Li et al 2010;Lu et al 2011;Tang et al 2009).…”
Section: Introductionmentioning
confidence: 99%